Uljabuouda vindkraftpark turbinmodellering och stabilitetsanalys - Lenasson, Magnus (Chalmers tekniska högskola / Institutionen för energi och miljö, 2007)
This master thesis has been performed at Solvina in Gothenburg for Skellefteå Kraft and Vattenfall Eldistribution. The aim of it is to investigate the consequences of the installation of a wind power plant on the mountain Uljabuouda in the vicinity of Arjeplog. Especially the impacts on voltage and transient stability are examined. Furthermore, the amount of extra strain on the voltage regulation equipment and the needs for increased regulation capabilities are looked into. The wind power plant is planned to be built by Skellefteå Kraft and connected to a 130 kV grid owned by Vattenfall Eldistribution. The work comprehends the following main parts: - Theoretical studies aimed at wind turbines and power system stability issues. - Modelling of the type of wind turbines assumed to be built on Uljabuouda. - Simulations of different operation cases and analysis of the simulation results. The results from the simulations show that, as far as voltage stability and extra workload on tap-changers are concerned, the wind power plant does not, in any significant manner, worsen the present conditions. The problem of overloading the line between Arvidsjaur and Vargfors is also minor. During the worst year for which measurement results have been obtained 7,4 MWh would have had to be disconnected, which is practically nothing in comparison with the annual hydro power production in the area, 250-300 GWh. Larger problems arise when it comes to the matter of transient stability. The synchronous generators in the system can during deep voltage dips, depending on the circumstances, stay synchronized approximately 0.3 seconds. However, the undervoltage protections on the predicted type of wind turbines trips after only 0.08 seconds. This sudden trip makes the plant incapable of meeting Svenska kraftnäts (The Swedish TSO’s) demands on disturbance tolerance. To be able to fulfill those demands the protections are required to have an operation time of at least 0.25 seconds for protection levels higher than 60 %. Recommended future ...